Relationship between alcohol use and overactive bladder disease: a cross-sectional study of the NHANES 2005–2016 - Yixin Zhang; Weijun Qin (Frontiers in Public Health)
BackgroundOveractive bladder syndrome (OAB) is a prevalent urological condition which has a substantial impact on the life quality of affected individuals, resulting in restrictions in daily activities and work productivity. Alcohol is a diuretic, which means that it increases urine production and can potentially worsen urinary urgency and frequency. Several studies have investigated the association between alcohol consumption and OAB symptoms, but the results have been conflicting. This study aimed to investigate the relationship between alcohol consumption and OAB symptoms using a large, nationally representative sample.MethodData from the National Health and Nutrition Examination Survey 2005–2016 were obtained for analysis. The Overactive Bladder Symptom Scale (OBSS) was used to determine the presence of OAB in each participant. Multivariate logistic regression and ordinal logistic regression were used to analyze the association of alcohol use frequency and quantity with the onset and severity of OAB, respectively.ResultsA total of 7,805 samples (representing the 1,473,525,341 US population after weighting) were included in our analysis. Approximately 12.4% of this weighted sample self-reported having OAB. A greater proportion of nondrinkers, a higher proportion of females, higher blood pressure, older age, and lower income levels were observed in OAB patients compared to non-OAB patients. Univariate logistic regression revealed that the risk of OAB was significantly greater in the nondrinker group than in the 1–5 drinks/month (OR 0.64; 95% CI, 0.50–0.83), 5–10 drinks/month (OR 0.60; 95% CI, 0.43–0.82) and 10+ drinks/month groups (OR 0.41; 95% CI, 0.30–0.56) and the risk of OAB in the lowest quartile of alcohol consumption quantity was significantly higher than the second (OR 0.58; 95% CI, 0.47–0.70), third (OR 0.49; 95% CI, 0.39–0.62), and highest quartiles groups (OR 0.58; 95% CI, 0.45–0.75). The adjusted model revealed that only patients in the 10+ drinks/month group had a significantly lower risk of OAB than did those in the nondrinker group (OR = 0.64; 95% CI = 0.45–0.92), while the other two groups had similar risks. Furthermore, no significant association was found for the highest quartiles in the adjusted model; however, the second and third quartiles of alcohol consumption quantity group still exhibited obvious associations. These findings suggest that higher alcohol consumption, when appropriate, is associated with a lower risk of OAB compared to nondrinkers and the lowest quartile of alcohol consumption quantity group, even after adjusting for age, sex, race, and comorbidities.ConclusionIn conclusion, our findings revealed a significant association between alcohol consumption and the incidence of OAB in the study population. In terms of long-term effects, alcohol may not be a risk factor for OAB. These factors may represent intervention targets for lowering the risk and severity of OAB symptoms, but this needs to be confirmed in large clinical trials.